Treatment for Uncomplicated Plasmodium falciparum Malaria in French Soldiers Deployed in Sub-Saharan Africa: Gaps Between Policy and Field Practice. Issue 9 (7th February 2018) - Perisse, Anne; Velut, Guillaume; Javelle, Emilie; Loarer, Gwion; Michel, Remy; Simon, F
Abstract: Background: Malaria prevention and treatment are big challenges for the French forces deployed in sub-Saharan Africa. Since December 2013, 1, 800 French soldiers have been deployed at any one time in the Central African Republic in the framework of "Operation Sangaris" and European Union Force (EUFOR). Over the 2014–2015 period, about 500 cases of malaria were notified in these troops during the operation or after their return (annual incidence: 13.4 p.100 person-year). The recommendation to use dihydroartemisinin-piperaquine (DHA-PQ) as the first-line treatment for French soldiers suffering from uncomplicated Plasmodium falciparum malaria in endemic areas is not always followed in practice in the field by French military general practitioners (GPs). Methods: We conduced a retrospective Knowledge-Attitude-Practice study by self-administered questionnaire, to all military French doctors who were in mission in Central African Republic from January 2014 to July 2015 to try to understand what were the reasons for the GP not to prescribe DHA-PQ on the field. Findings: Thirty-six GPs (53%) answered to the questionnaire. Eighty-three percent of them knew about the recommendation to use DHA-PQ for un uncomplicated Pf malaria. Fifty-eight percent had a favorable attitude toward DHA-PQ. The factors associated with the prescription of another drug (Atovaquone-proguanil) were: the habit (odds ratio [OR] 0.1, confidence interval (CI) 0–0.6], the fact that Atovaquone-proguanil is more practical to use [OR 0.01, CI 0–0.1]. In practice, only 37.5% prescribed DHA-PQ the most of the time during their mission. Factors associated with a non-favorable attitude toward DHA-PQ were: the necessity to calculate a QTc interval during the treatment [OR 0.2, confidence interval 0–0.9], and the fact that DHA-PQ must be taken on an empty stomach [OR 0.3, CI 0.1–0.8]. GP who received a formation before their mission about malaria and treatment had a favorable attitude toward DHA-PQ. Discussion: There is very satisfactory knowledge by the military GPs stationed in the Central African Republic on both the recommendations and prescription of antimalarial drugs. The present study highlights some difficulties in implementing the recommendations in an operational context, notably factors limiting the prescription of DHA-PQ during military deployment (need for ECG monitoring, empty stomach, and lack of habit). Proposals can be made to improve the efficacy, tolerance, and practicability of malaria treatment in the field. The main focus should be a more flexible application of the French DHA-PQ risk management plan in the field, specific training and communication about DHA-PQ use, the generalization of ECG printing equipment in the field, and the switch from DHA-PQ to an alternative artemisinin-based combination therapy during deployments in malaria-endemic areas.